MA Defence: â€œTweeting Tsunami: Early Warning Networks in British Columbiaâ€ by Amanda Oldring - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Amanda Oldring, will defend her MA Thesis on Wednesday, December 16, 2015 at Harbour Centre, Room 1500 (1:00 pm - 3:00 pm). Here is the abstract of her thesis “Tweeting Tsunami”: